2023
DOI: 10.3389/feart.2022.1055480
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic structure of the Australian continent

Abstract: The Australian continent preserves some of the oldest lithosphere on Earth in the Yilgarn, Pilbara, and Gawler Cratons. In this study we present shear wave splitting and Ps receiver function results at long running stations across the continent. We use these results to constrain the seismic anisotropic structure of Australia’s cratons and younger Phanerozoic Orogens. For shear wave splitting analysis, we utilize SKS and SKKS phases at 35 broadband stations. For Ps receiver function analysis, which we use to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 97 publications
2
2
0
Order By: Relevance
“…This is consistent (within typical errors) with our previous study of permanent station MULG (Φ: 79°, δt: 1.1 s) located within the Gawler Craton (Eakin et al, 2021). Other recent studies have reported a similar NE-SW to ENE-WSW trend over the South Australian Craton (Ba et al, 2023;Birkey & Ford, 2022). The spatial extent of this shear-wave splitting pattern, throughout the Gawler Craton and extending eastwards into the Curnamona Province, can now be seen more clearly.…”
Section: Sks and Pks Splitting Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent (within typical errors) with our previous study of permanent station MULG (Φ: 79°, δt: 1.1 s) located within the Gawler Craton (Eakin et al, 2021). Other recent studies have reported a similar NE-SW to ENE-WSW trend over the South Australian Craton (Ba et al, 2023;Birkey & Ford, 2022). The spatial extent of this shear-wave splitting pattern, throughout the Gawler Craton and extending eastwards into the Curnamona Province, can now be seen more clearly.…”
Section: Sks and Pks Splitting Resultssupporting
confidence: 91%
“…This orientation is very similar to the APM of the Australian plate, ∼6 cm per year at 21° (clockwise from North) in this location, as indicated by the black arrow in Figure 3. Hints of such a correspondence between the fast direction and the APM for eastern Phanerozoic Australia have been previously noted based on more limited results (Ba et al, 2023;Bello et al, 2019;Birkey & Ford, 2022). The results of our analysis confirm a similarity between the splitting fast direction and the APM for southeastern Australia that is spatially distinct from the pattern over cratonic Australia.…”
Section: Sks and Pks Splitting Resultssupporting
confidence: 85%
See 2 more Smart Citations